Reliability and Validity of Light-Intensity Physical Activity Scales in Adults: A Systematic Review. Issue 2 (3rd April 2023) - Tanaka, Rumi; Yakushiji, Kanako; Tanaka, Satomi; Tsubaki, Michihiro; Fujita, Kimie
ABSTRACT: This study aimed to review the validity and/or reliability of light-intensity physical activity (LPA) questionnaires and identify the most suitable questionnaires for measurement of LPA in adults. Following the PRISMA-P 2020 guidelines, we searched MEDLINE, PsycINFO, CINAHL, Scopus, Embase, and MedNar. Only studies that targeted adults ≥18 years old and used LPA measured by accelerometer and/or heart rate monitor as an objective criterion were included. The search resulted in 2748 article hits, from which we extracted 16 studies with 14 questionnaires. The 7-Day Sedentary and LPA Log and LPA Questionnaire were specifically designed for LPA measurement, and the Community Health Activities Model Program for Seniors physical activity self-report questionnaire scale has been revised for LPA measurement. These questionnaires had comparatively high reliability and validity in this review. Most studies contained methodological limitations such as test-retest period. In the future, more accurate reliability/validity studies should be conducted for each questionnaire.